Terapi Story Telling dan Menonton Animasi Kartun terhadap Ansietas - Padila Padila; Agusramon Agusramon; Yera Yera (Journal of Telenursing (JOTING), 2019)
This study aims to determine the comparison of the effectiveness of story telling therapy and watching animated cartoons on the level of anxiety due to hospitalization in preschool aged children at the hospital. Raflesia Bengkulu City. This study used a quasi experimental design of two groups before after or pre-test and post test group. The results showed that the treatment using story telling (storytelling) was more significant in reducing anxiety in pre-school age children at Raflesia Hospital, Bengkulu City compared to watching cartoon animation, seen from the value of the t-test results of the Independent sample, the mean value of posttest results was 5. between story telling therapy and watching cartoon animation, namely 2.00 and 8.00. In conclusion, story telling is six times faster to reduce anxiety (anxiety) in pre-school children during hospitalization compared to watching cartoon animation therapy. Keywords: Cartoon Animation, Anxiety, Pre School, Story Telling